PENGARUH MEDIA GAME PUZZLE TERHADAP KEMAMPUAN MENULIS AKSARA SUNDA KELAS VII MTS AL HIDAYAH JAMANIS KABUPATEN TASIKMALAYA - Abdillah, Helmy; Ropiah, O.; Triwahyuni, Heti (Prodi Pendidikan Bahasa dan Sastra Daerah, 2018)
This study has a background of the lack of knowledge of students in writing the Sundanese script MTs Al Hidayah Jamanis Tasikmalaya District. Therefore, researchers meliki purpose of researching students' writing skills in script Sunda (1) write a script swara / vocal, (2) writing script Ngalagena, (3) write a script pangwilang, and (4) write rarangkén. This research uses quantitative approach. The method used is quasi experimental method with pre-test and post-test design. Sources of data in the study were students of class VII MTs Al Hidayah Jamanis Tasikmalaya District amounted to 23 students. The result of this research shows the improvement of students' ability in writing Sundanese script. This can be seen from the results of hypothesis testing. The average value of students prior to using the media puzzle games which is 72 while after using the media puzzle games average student scores be 76. Additionally, the increased ability to write Sundanese script can be seen from the results of hypothesis testing tshowed 6,15 > ttable 2,46. That is, there is a significant difference between learning outcomes before and after using media puzzle games.